Thoughts of Umbanda's Religionists in the City of Rio de Janeiro about the COVID-19 pandemic: interfaces between religion, health and society (Research, Society and Development, 2020)
2020 was marked by the COVID-19 pandemic, characterized by the high number of infections and deaths around the world and, as the knowledge about the virus is still low, it is comprehensible that people consider hypotheses, share beliefs and thoughts in the society, crossed by several areas through the information received and disseminated. In this regard, the Umbanda in Brazil, with its particularities, worldview and cosmogony operating in situations of health and illness, demonstrates its own knowledge and capable of guiding the behaviors and attitudes of its religionists through shared beliefs, which is relevant to investigate. So, the objective of this study is to analyze the thinking of Umbanda's religionists in the city of Rio de Janeiro about the pandemic of COVID-19 and its influence in the confrontation of the disease. In this way, this is an exploratory research, performed by Google Forms, with 100 attendees who live in Rio de Janeiro, mostly women, with an average age over 40 years. The results achieved reveal that the attendees have religious beliefs to understand and explain the COVID-19 pandemic and its interaction with the earth, human beings, stages of evolution of humans and the world in which they live, besides to aspects related to evil's personification in this context. However, they don't attribute to the religion, the exclusive solution for the current scenario, but rather to scientific discoveries, which also guide their preventive health practices in relation to the pandemic and refute the beliefs that the virus was created in laboratory.